2020
DOI: 10.1021/acscombsci.0c00096
|View full text |Cite
|
Sign up to set email alerts
|

High Entropy and Sluggish Diffusion “Core” Effects in Senary FCC Al–Co–Cr–Fe–Ni–Mn Alloys

Abstract: alloy exhibited a lower free energy of mixing, i.e., higher thermodynamic stability, than equiatomic Al x CoCrFeNiMn compositions, at 1100 °C and above. Therefore, the role of enthalpy was estimated to be significant in achieving higher thermodynamic stability in off-equiatomic alloys, since they always have lower entropy of mixing than their equiatomic counterparts. The magnitude of interdiffusion coefficients of individual elements in Al−Co−Cr−Fe−Ni−Mn alloys were compared to the interdiffusion coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…whereD eff i is the average effective interdiffusion coefficient of component i for the composition range, C i (x 1 ) to C i (x 2 ). The detailed procedure for the determination ofD eff i and limitations of using the Boltzmann-Matano method extended to a multi-component system to determine the main and cross interdiffusion coefficients, specifically for HEAs, have been documented previously by Mehta and Sohn [15,16]. Figure 1(a-d Tracer diffusion coefficient can be measured using the analytical formalism proposed by Belova et al [26]: where a is a constant and the value of G 2 can be determined using:…”
Section: Results and Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…whereD eff i is the average effective interdiffusion coefficient of component i for the composition range, C i (x 1 ) to C i (x 2 ). The detailed procedure for the determination ofD eff i and limitations of using the Boltzmann-Matano method extended to a multi-component system to determine the main and cross interdiffusion coefficients, specifically for HEAs, have been documented previously by Mehta and Sohn [15,16]. Figure 1(a-d Tracer diffusion coefficient can be measured using the analytical formalism proposed by Belova et al [26]: where a is a constant and the value of G 2 can be determined using:…”
Section: Results and Analysesmentioning
confidence: 99%
“…spike profile) overlaid on each other, and the corresponding Gaussian fitted profile obtained after mathematical subtracting the spike profile from the interdiffusion profile at 900°C, 950°C and 1000°C. [20], CoCrFeNiMn [20], AlCoCrFeNi [15], and AlCoCrFeNiMn [16] FCC alloys. alloys.…”
Section: Results and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermodynamically, HEAs would have a high configurational entropy of mixing, and therefore form in a simple solid solution instead of complex low entropy, enthalpy-driven intermetallic phases. [1] However, various researchers [2][3][4] had previously cast doubt on this theory of entropic stabilizations and suggested that the role of enthalpy of mixing cannot be neglected in the stability of a single phase. It has also been observed that prolonged annealing of HEAs (e.g., CoCrFeNiMn) can result in decomposition at intermediate temperatures (* 500-900 °C).…”
Section: Introductionmentioning
confidence: 99%